Enteric Pathogen Bacteria in Non-Broiler Chicken Egg Shells from Traditional Market and Supermarket, Jatinangor Subdistrict, West Java - Kavita Arumugam; Sunarjati Sudigdoadi; Gaga Irawan Nugraha (Althea Medical Journal, 2015)
Background: Around 1.5 million of children dying annually due to diarrhea. Contaminated food is one of the sources of the diarrhea incidence (food borne diseases). Eggs are one of the least expensive forms of protein which is affordable by the community and is easily to find in either traditional or modern market/supermarkets.The objective of this study was to identify enteropathogenic bacteria contamination on non-broiler (ayam kampung) egg shell and to compare the findings between eggs sold in traditional and modern markets.Methods: This was a descriptive study performed at the Microbiology Laboratory of the Faculty of Medicine, Universitas Padjadjaran. A total of 40 eggs were used, 20 from two traditional markets and 20 from two modern markets. The eggs were swabbed using saline, dipped in tryptic soy broth and streaked on Mac Conkey agar. The collected data were analyzed and presented in tables.Results: Out of 40 samples, there were 19 positive cultures found from the traditional market and 16 from the modern market. There were 30 pink colonies indicating that they were lactose fermented, 5 transparent colonies indicated non-lactose fermentation, 4 showed no colony growth, and 1 grew an unidentified colony. The most found bacteria were Klebsiella sp. and Enterobacter sp. in both market. Conclusions: Eggs shells from traditional and modern markets are contaminated with Enteropathogenic microbes. DOI: 10.15850/amj.v2n3.487